From cooling water war to cooling towers: transnational water diplomacy around the allocation of nuclear cooling on the Aare and Rhine Rivers, 1965-1972 - Gutting, Alicia (2025)
This article explores the efforts of Germany and Switzerland, from 1965 to 1972, to mitigate thermal pollution caused by nuclear power plants along the Aare and Rhine Rivers. Despite the initial promise of nuclear energy, concerns about its environmental impact, specifically on water quality, led both countries to collaboratively set temperature limits for cooling water discharge from nuclear power plants. In contrast to the predominant focus on anti-nuclear protests in the existing literature, this article highlights the cooperative aspects of cross-border management, revealing a concerted effort to balance the utilisation of river cooling capacities while safeguarding water quality. The article contributes to the evolving field of water diplomacy, challenging the notion of inevitable conflicts by showcasing a joint approach to addressing shared environmental challenges.